Pain Assessment of Elderly Patients with Cognitive Impairment in the Emergency Department: Implications for Pain Management-A Narrative Review of Current Practices - Joshua Jones; Tin Fei Sim; Jeff Hughes (MDPI AG, 2017)
Elderly people are susceptible to both falls and cognitive impairment making them a particularly vulnerable group of patients when it comes to pain assessment and management in the emergency department (ED). Pain assessment is often difficult in patients who present to the ED with a cognitive impairment as they are frequently unable to self-report their level of pain, which can have a negative impact on pain management. This paper aims to review how cognitive impairment influences pain assessment in elderly adults who present to the ED with an injury due to a fall. A literature search of EMBASE, ProQuest, PubMed, Science Direct, SciFinder and the Curtin University Library database was conducted using keyword searches to generate lists of articles which were then screened for relevance by title and then abstract to give a final list of articles for full-text review. Further articles were identified by snowballing from the reference lists of the full-text articles. The literature reports that ED staff commonly use visual or verbal analogue scales to assess pain, but resort to their own intuition or physiological parameters rather than using standardised observational pain assessment tools when self-report of pain is not attainable due to cognitive impairment. While studies have found that the use of pain assessment tools improves the recognition and management of pain, pain scores are often not recorded for elderly patients with a cognitive impairment in the ED, leading to poorer pain management in this patient group in terms of time to analgesic administration and the use of strong opioids. All healthcare professionals involved in the care of such patients, including pharmacists, need to be aware of this and strive to ensure analgesic use is guided by appropriate and accurate pain assessment in the ED.